The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1938
DOI: 10.1152/ajplegacy.1938.123.2.412
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Composition of Sweat During Acclimatization to Heat

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

1947
1947
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(50 citation statements)
references
References 0 publications
4
46
0
Order By: Relevance
“…3 the sweat rate is plotted against the creatinine concentration for subject G.; the regression line is also shown. (Ladell, 1945b); a number of other authors have also reported that the greater the sweat rate the more nearly does the chloride content of the sweat approach that of the plasma (Dill, Hall & Edwards, 1938;Johnson, Pitts & Consolazio, 1944). There would therefore appear to be two mechanisms at least involved in the production of sweat from body fluids.…”
Section: Resultsmentioning
confidence: 97%
“…3 the sweat rate is plotted against the creatinine concentration for subject G.; the regression line is also shown. (Ladell, 1945b); a number of other authors have also reported that the greater the sweat rate the more nearly does the chloride content of the sweat approach that of the plasma (Dill, Hall & Edwards, 1938;Johnson, Pitts & Consolazio, 1944). There would therefore appear to be two mechanisms at least involved in the production of sweat from body fluids.…”
Section: Resultsmentioning
confidence: 97%
“…This renders the modelling of sweat composition more complex. Indeed, when one realises that sweat sodium concentrations, for instance, can double in some individuals over the physiological range for sweat production [245-248], then it becomes apparent that quoting sweat compositions without simultaneously reporting glandular or whole-body sweat flow offers little useful information. However, when normalised to sweat flow, sodium losses appear to be independent of gender and can be described using a common flow-dependent relationship ( N = 12, 36°C, 50% relative humidity, r 2 = 0.94 [248]), at least within young, physically active, unacclimatised individuals:…”
Section: Reviewmentioning
confidence: 99%
“…The minimum repellency concentration of L-LA in our experiments was Ϸ41.7 ppm, lower than that present on human skin. Furthermore, Dill et al (1938) and van Heyningen and Weiner (1952) found that the amount of LA in arm sweat was 1.5-to threefold greater than in total body sweat. Therefore, the concentration of L-LA applied to the skin in our experiments might actually be higher when added to the natural amount of LA on forearms.…”
Section: Resultsmentioning
confidence: 97%